Program Perbaikan Instalasi Listrik Dan Fasilitas Pendukung Berbasis Komunitas Lokal Di Wisata Terintegrasi Gunung Jae Lombok Barat - Ariel Apriansyah; Made Sutha Yadnya; Cipta Ramadhani; Agustono Setiawan; Ehza Jumiati; A. Sjamsjiar Rachman; I Nyoman Wahyu Satiawan (Jurnal Gema Ngabdi, 2026)
Gunung Jae Tourism Area in Sedau Village, West Lombok Regency, is a natural tourist destination that continues to develop but still faces limitations in basic infrastructure, particularly electrical installations and street lighting systems. These limitations reduce visitor safety, comfort, and restrict nighttime tourism activities. This community service program aimed to improve electrical infrastructure through electrical installation upgrades and the implementation of a community-based Street Lighting System (SLS). The implementation methods included site surveys, technical planning, material preparation, system installation, and functional testing. The program was carried out over two days involving lecturers, students, and local communities through a participatory approach. The results showed that the street lighting system was successfully installed and operated according to lighting standards. The program improved nighttime visibility in the tourism area, enhanced visitor safety, and supported local economic activities based on tourism development. In addition, the program strengthened students’ technical competencies and increased community awareness regarding safe, efficient, and sustainable electrical infrastructure management.